Development of a quad-copter platform for map building in unknown environment - Koh, Rui Chen (2015)
This project consist of the hardware and software components of an autonomous quad-copter. For the hardware component of the project, it focused on both the designing of the quad-copter frame and manufacturing of the supporting parts on the quad-copter. The design of the main frame was based on an existing Droidworx quad-copter and it was created on the 3D Computer Aided Design (CAD) Solidworks software. The various components that contributes to the quad-copter were created individually and combined together to form an assembly of the final quad-copter frame. In addition, supporting parts for the sensors and circuit boards to be attached on board the quad-copter were designed with the use of Solidworks. These parts were manufactured through the 3D Printing process and test fitted on the quad-copter. The software component of the project emphasizes on the implementation of a simulation program that simulates the quad-copter navigating autonomously through an indoor environment. The simulation program was implemented with the Simultaneous Localization and Mapping (SLAM) technique in the Robot Operating System (ROS) to provide the quad-copter with autonomous navigation capability. SLAM technique allows for localization and mapping of the quad-copter in an unknown indoor environment. With this technique, the quad-copter will be able to successfully navigate autonomously through the environment. A laser range finder was incorporated to localize the quad-copter and concurrently to create a virtual map of the surrounding. Through ROS, the SLAM technique was implemented through the use of the Gmapping algorithm. The Gmapping algorithm subscribes to the topic published by the laser range finder and reads the laser data for the construction of a virtual map in ROS. The map was visualized on the rviz 3D visualization tool in ROS. With rviz, path planning was executed to provide guidance and obstacle avoidance operation which allows the quad-copter to navigate safely through the unknown environment. This report will highlight the work and research done by the student throughout the final year project. The student had spent a significant amount of time learning the Solidworks software and ROS before the implementation of the project. In the subsequent sections, the report will provide a detailed coverage of the research and results of the implementation done by the student.